Design and Development of a Lead-Freepiezoelectric Energy Harvester for Wideband, Low Frequency, and Low Amplitude Vibrations - Neetu Kumari; Micky Rakotondrabe (Micromachines, 2021)
In recent years, energy harvesting from ambient vibrations using piezoelectric materials has become the center of attention due to the fact that it has the potential to replace batteries, providing an easy way to power wireless and low power sensors and electronic devices. Piezoelectric material has been extensively used in energy harvesting technologies. However, the most commercially available and widely used piezoelectric materials are lead-based, Pb<semantics> [ZrxTi1−x]</semantics> <semantics>O3 </semantics>(PZT), which contains more than 60 weight percent lead (Pb). Due to its extremely hazardous effects on lead elements, there is a strong need to substitute PZT with new lead-free materials that have comparable properties to those of PZT. Lead-free lithium niobate (LiNbO3) piezoelectric material can be considered as a substitute for lead-based piezoelectric materials for vibrational energy scavenging applications. LiNbO3 crystal has a lower dielectric constant comparison to the conventional piezoceramics (for instance, PZT); however, at the same time, LiNbO3 (LN) single crystal presents a figure of merits similar to that of PZT, which makes it the most suitable choice for a vibrational energy harvester based on lead-free materials. The implementation was carried out using a global optimization approach including a thick single-crystal film on a metal substrate with optimized clamped capacitance for better impedance matching conditions. A lot of research shows that standard designs such as linear piezoelectric energy harvesters are not a prominent solution as they can only operate in a narrow bandwidth because of their single high resonant peak in their frequency spectrum. In this paper, we propose, and experimentally validate, a novel lead-free piezoelectric energy harvester to harness electrical energy from wideband, low-frequency, and low-amplitude ambient vibration. To reach this target, the harvester is designed to combine multi-frequency and nonlinear techniques. The proposed energy harvesting system consists of six piezoelectric cantilevers of different sizes and different resonant frequencies. Each is based on lead-free lithium niobate piezoelectric material coupled with a shape memory alloy (nitinol) substrate. The design is in the form of a circular ring to which the cantilevers are embedded to create nonlinear behavior when excited with ambient vibrations. The finite element simulation and the experimental results confirm that the proposed lead-free harvester design is efficient at low frequencies, particularly different frequencies below 250 Hz.